Comparison of microleakage of an alkasite restorative material, a composite resin and a resin-modified glass ionomer - Fariba Motevasselian; Hamid Kermanshah; Ebrahim Rasoulkhani; Mutlu Özcan (Brazilian Journal of Oral Sciences, 2021)
Aim: To compare the microleakage of Cention N, a subgroup of composite resins with a resin-modified glass ionomer (RMGI) and a composite resin. Methods: Class V cavities were prepared on the buccal and lingual surfaces of 46 extracted human molars. The teeth were randomly assigned to four groups. Group A: Tetric N-Bond etch-and-rinse adhesive and Tetric N-Ceram nanohybrid composite resin, group B: Cention N without adhesive, group C: Cention N with adhesive, and group D: Fuji II LC RMGI. The teeth were thermocycled between 5°-55°C (×10,000). The teeth were coated with two layers of nail vanish except for 1 mm around the restoration margins, and immersed in 2% methylene blue (37°C, 24 h) before buccolingual sectioning to evaluate dye penetration under a stereomicroscope (×20). The data were analyzed by the Kruskal-Wallis and Wilcoxon tests (α=0.05). Results: Type of material and restoration margin had significant effects on the microleakage (p<0.05). Dentin margins showed a higher leakage score in all groups. Cention N and RMGI groups showed significant differences at the enamel margin (p=0.025, p=0.011), and for the latter group the scores were higher. No significant difference was found at the dentin margins between the materials except between Cention N with adhesive and RMGI (p=0.031). Conclusion: Microleakage was evident in all three restorative materials. Cention N groups showed similar microleakage scores to the composite resin and displayed lower microleakage scores compared with RMGI.